Producing paramedicine: Case studies in the medical labor process - Seim, Josh; Corman, Michael; McCann, Leo (Social science & medicine (1982), 2022)
How is medical labor power, that being the capacity to assemble, adjust, or arrange medical subjects, converted into medical practice? Drawing on three qualitative case studies in the United States, Canada, and the United Kingdom, we argue that this conversion is shaped by pressures channeled through the relations that medical workers enter into with patients “from below” and managers “from above.” We demonstrate this by examining a common empirical object: ambulance labor. In addition to providing a unique window into the varieties of medical work, paramedicine offers a strategic venue for examining the kinds of productive relations that medical laborers enter into. Our research shows how the labor process is shaped by patient requests that can either conform or contradict workers’ shared sense of vocation. We also detail how this same process is simultaneously pressured by managers who are generally focused on increasing both the flexibility and the visibility of their workers. Many of these pressures, we argue, can be linked to common forces of neoliberalism across our three nations. Our analysis of the medical labor process inspires some practical recommendations to reform ambulance-based care. However, our primary aim is to advance a labor-centric approach to studying medicine. •Examines medicine as a labor process through three case studies of ambulance work.•Unique pressures shape the conversion of medical labor power into medical practice.•Ambulance workers in U.S., Canada, and UK are pressured by patients “from below.”.•Those same workers are also pressured by managers “from above.”.•These pressures are linked to common forces of neoliberalism across our cases.